Numerical simulation with MATLAB and Probit models to calculate the consequences due to lung damage from boiler explosions - Morales-Vargas, Ricardo Alberto (2024)
Boiler explosions around the world cause serious damage to work facilities as well as injuries to operators, which can range from burns and lacerations to death, with high economic costs for user companies. In industrial and institutional environments, the main cause of boiler explosions is low water level, which causes boiler tube overheating, sudden vaporization, pressure rise, and catastrophic failure. Despite these risks, there are few computational tools to calculate their consequences. Preventing this type of accident is essential in industry and commerce, as well as the service sectors since these must be intrinsically safe to fulfill their economic and humanitarian mission, respectively. This article reviews the technical requirements for safe operation of boilers focusing on correct location and distancing from the boiler room to minimize the domino effect and human injuries. The author developed a script and compiled code in the MATLAB® environment to calculate the resulting maximum overpressure as a function of distance, with user-entered parameters for a variety of boilers and explosion conditions. Shock wave damage was estimated using Probit calculations considering lung damage, to facilitate analysis and recommend the ideal or improved location of the boiler room or compartment. It is concluded that regulations must include a mandatory analysis of consequences, using similar or more elaborate numerical models, to guide the distribution of plants and protect workers and neighbors from explosion overpressure effects.